A Comparative Study of Connotative meanings of “LI” in Mandarin and “NAI” in Thai - Chalanuson, Yanakorn (Journal of Sinology (วารสารจีนวิทยา), 2015)
The purpose of this article is to study and compare the connotative meanings of “LI” in Mandarin Chinese and “NAI” in Thai, by employing a cognitive semantics approach to analyze and explain the meaning. The results of this research reveal seven connotative meanings of the direction word “LI” that indicate that an object lies within the boundaries of : 1) human society, 2) time, 3) metaphorical meaning, 4) members or departments of an administrative district, 5) a plural number, 6) information sources, and 7) a condition or feature. However, there are eleven connotative meanings of Thai preposition “NAI” that indicate that an object lies within the boundaries of : 1) human society, 2) time, 3) metaphorical meaning, 4) an action process, 5) a condition or feature, 6) clothing, 7) a plural number, 8) possession, 9) age, 10) information sources, 11) the meaning of verbs. By contrasting “LI” in Mandarin Chinese and “NAI” in Thai preposition, the author indicates six similar meanings wherein an object lies: “within the boundaries of human society”, “within the boundaries of time”, “within the boundaries of metaphorical meaning”, “within the boundaries of a condition or feature”, “within the boundaries of a plural number”, and “within the boundaries of information sources”. Additionally, the author indicates six meanings that differ when indicating an object lies: “within the boundaries of members or departments of an administrative district”, “within the boundaries of an action process”, “within the boundaries of clothing”, “within the boundaries of the possession”, “within the boundaries of age”, and “within the boundaries of the meaning of verbs”. The different meanings of “LI” in Mandarin Chinese and “NAI” in Thai occurred as extensions of meanings within a metaphor process which is one process in cognitive semantics.